Totally endoscopic aortic valve replacement with concomitant trans-aortic mitral valve repair for mitral regurgitation - Antonios Pitsis; Nikolaos Tsotsolis; Harisios Boudoulas; Konstantinos Dean Boudoulas (Journal of Cardiothoracic Surgery, 2021)
Abstract Background Minimally invasive aortic valve procedures through a hemi-sternotomy or a right anterior mini-thoracotomy have gained popularity over the last several years. Totally endoscopic aortic valve replacement (TEAVR) is an innovative and a less invasive (incision-wise) surgical aortic valve replacement technique. The operative steps of TEAVR have been reported previously from our group. Mitral regurgitation (MR) frequently accompanies aortic valve disease that at times may also require repair. Totally endoscopic surgery in such cases has not been tested. Presentation of the technique We present a surgical technique for a totally endoscopic approach to aortic valve replacement and concomitant mitral valve repair for primary and secondary MR. An aortotomy incision was used avoiding an atriotomy, which results in an increase in cross-clamp (XC) and cardiopulmonary bypass (CPB) times that could be associated with higher mortality and morbidity. Neochords (artificial chordae tendineae) were used for primary MR and an edge-to-edge approach for secondary MR. Conclusion TEAVR and concomitant mitral valve repair can be performed successfully with reasonable XC and CPB times with excellent short-term results.